Heidegger's life and thought a tarnished legacy - O'Brien, Mahon (Rowman & Littlefield International, 2020)
Martin Heidegger was a captivating and controversial philosopher, known for his highly original and challenging philosophical concepts, as well as his association with -- and sympathy for -- the Nazi Party during World War II. Providing an introduction to both the man and his philosophy, this book is a concise, jargon-free journey through his life and thought. The publication of Heidegger's private 'Black Notebooks' from the 1930s and 40s has led to renewed interest in the relationship between Heidegger's philosophy and his political views and caused widespread confusion and condemnation. This short book puts many of these problems into context and offers an honest appraisal of Heidegger's disturbing political views and how they might relate to some of the perennial themes that occupied his philosophical imagination. A fascinating portrait of a brilliant, complicated and often unattractive human being, the book will prove invaluable for students with some familiarity with Heidegger's thought, students approaching Heidegger's work for the first time and non-specialists looking to acquaint themselves with a great, yet problematic, twentieth century thinker.